Synchrotron microComputed tomography of the mature bovine dentinoenamel junction - Stock, S. R.; Vieira, A. E. M. [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Cannon, M. L.; Xiao, X.; De Carlo, F. (Academic Press Inc. Elsevier B.V., 2008)
The mature dentinoenamel junction (DEJ) is viewed by some investigators and the current authors, not as a fossilized, sharp transition between enamel and dentin, but as a relatively broad structural transition zone including the mantle dentin and the inner aprismatic enamel. In this study, the DEJ structure in bovine incisors was studied with synchrotron microComputed Tomography (microCT) using small cubes cut parallel to the tooth surface. The reconstructions revealed a zone of highly variable punctate contrast between bulk dentin and enamel; the mean linear attenuation coefficients and their standard deviations demonstrated that this zone averaged less mineral than dentin or enamel but had more highly variable structure than either. The region with the punctuate contrast is, therefore, the mantle dentin. The thickness of the mantle dentin seen in a typical data set was about 30 mu m, and the mantle dentin-enamel interface deviated +/- 15 mu m from the average plane over a distance of 520 mu m. In the highest resolution data (similar to 1.5 mu m isotropic voxels, volume elements), tubules in the dentin could be discerned in the vicinity of the DEJ. Contrast sensitivity was high enough to detect differences in mineral content between near-surface and near-DEJ volumes of the enamel. Reconstructions before and after two cubes were compressed to failure revealed cracks formed only in the enamel and did not propagate across the mantle dentin, regardless of whether loading was parallel to or perpendicular to the DEJ. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: microCT; dentinoenamel junction (DEJ); dentin; enamel; tooth; synchrotron X-radiation; computed tomography; microtomography